Meningkatkan Hasil Belajar Lari 60 Meter Melalui Pendekatan Bermain Pada Siswa Kelas V SD Negeri 2 Masohi Kabupaten Maluku - Siahaya, Frans; Hasbullah, Bahmid (MANGGUREBE: Journal Physical Education, Health and Recreation, 2022)
This study aims to determine whether there is an increase in the learning outcomes of running 60 meters through a playing approach for fifth grade students at SD Negeri 2 Masohi. The data obtained through classroom action research (CAR) was carried out in three cycles, namely cycles I, II and cycle III. Data for each cycle were obtained from observations and performance tests based on the indicators assessed in the assessment rubric. Furthermore, all scores obtained by each student, divided by the maximum score multiplied by one hundred percent (100%), will obtain the value of each student. This value is the final result obtained by each student which will determine whether the student is declared complete or not so that it can be continued in cycles II and III. After taking action in cycle I, the results of learning to run a distance of 60 meters with a playing approach were 28.76%. After being given action in cycle II, from 28.76% it rose to 67.87%, there was an increase of cycle III from 67.87% rose to 78.38% there was an increase of = 10.51%. Based on the results found in the implementation of the research described above, (Pupuh and M. Sobry Sutikno, 2007), explains that learning is essentially a "change" that occurs within a person after carrying out certain activities. Based on this theory, in the implementation of actions or learning carried out in 3 cycles, there are changes that occur in each cycle both in attitudes (affective), knowledge (cognitive) and skills (psychomotor). Thus it can be concluded that the play approach can be used to improve the learning outcomes of 60 meter running in class V SD Negeri 2 Masohi.